55-2x+3=4(x+6)+x

Simple and best practice solution for 55-2x+3=4(x+6)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 55-2x+3=4(x+6)+x equation:


Simplifying
55 + -2x + 3 = 4(x + 6) + x

Reorder the terms:
55 + 3 + -2x = 4(x + 6) + x

Combine like terms: 55 + 3 = 58
58 + -2x = 4(x + 6) + x

Reorder the terms:
58 + -2x = 4(6 + x) + x
58 + -2x = (6 * 4 + x * 4) + x
58 + -2x = (24 + 4x) + x

Combine like terms: 4x + x = 5x
58 + -2x = 24 + 5x

Solving
58 + -2x = 24 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
58 + -2x + -5x = 24 + 5x + -5x

Combine like terms: -2x + -5x = -7x
58 + -7x = 24 + 5x + -5x

Combine like terms: 5x + -5x = 0
58 + -7x = 24 + 0
58 + -7x = 24

Add '-58' to each side of the equation.
58 + -58 + -7x = 24 + -58

Combine like terms: 58 + -58 = 0
0 + -7x = 24 + -58
-7x = 24 + -58

Combine like terms: 24 + -58 = -34
-7x = -34

Divide each side by '-7'.
x = 4.857142857

Simplifying
x = 4.857142857

See similar equations:

| 2y^2-7x-15=0 | | 11n+10=6n | | (-3x^4y^5)62= | | -54-5x=-9+22 | | 8+5p-1=9p+23-2p | | 6n-7=2n-2 | | .17x+x=5000000 | | x+2x+12=0 | | 2x-5(x-4)=-5+4x-3 | | (x^2+5x-24)=(-x^2-4x+9) | | 9z^2+18z-48=0 | | 2797,04=(x*2140)/(3158,50*4) | | 4(t-4)+8t=6(2t+2)-8 | | 9z^2+18x-48=0 | | 23=5x-7x-1 | | 75.0=60+0.05t | | 6x^2+3=x | | 7-3(2x-1)=2x+2 | | 4(2x-1)=2x+26 | | 75.0=60+0.05 | | (4x-1)=(x+8) | | X^2=14+16x | | 5b+3-7b+8=1 | | -12+12x=9x+30 | | 3x-70= | | (2-x)=(8-x) | | b^2=5 | | 4(m-3)=16 | | -145+4x=-5+53 | | (3x+2y)(5x-3y)=0 | | 7+2m-4=7m-7-4m | | (a+2)=(3a+9) |

Equations solver categories